Investigation of the dynamic vertical behaviour of a floating pile embedded in unsaturated poroelastic half-space - Ma, Wenjie (2023)
This paper proposes an analytical solution for investigating the dynamic vertical behaviour of a floating pile in unsaturated poroelastic half-space by considering the dynamic properties of the soil below the pile base. The pile shaft resistance is derived by applying Hankel integral transformation to the governing equations, and the pile base resistance is derived by introducing the potential function and operator decomposition methods. The dynamic interaction between the soil and the pile is considered by virtue of the impedance function. To account for the mixed boundary conditions of the pile-soil interface, an analytical solution for the vertical dynamic response of a floating pile is derived in the frequency domain. Additionally, by utilizing the inverse Fourier transform and convolution theorem, a quasi-analytical solution for the velocity response of the floating pile is derived in the time domain. Furthermore, the derived solution is verified through comparisons with existing solutions available in the literature. Finally, a parametric study is performed to investigate the influence of saturation and intrinsic permeability on the dynamic flexibility coefficient of porous unsaturated half-space, the influence of saturation on the dynamic impedance of the soil layer, and slenderness ratio on the vertical behaviour of floating pile and end-bearing pile.